THE IMPACT OF DIGITAL MARKETING, SALES PROMOTION, AND ELECTRONIC WORD OF MOUTH ON CUSTOMER PURCHASE INTENTION AT TIKTOK SHOP - Elizabeth Putrinda Ratu; Joy Elly Tulung (Universitas Sam Ratulangi, 2022)
This research aims to analyze the impact of digital marketing, sales promotion, and electronic word of mouth on customer purchase intention at TikTok Shop in Manado. The independent variables used in this research are digital marketing, sales promotion, and electronic word of mouth, while the dependent variable is purchase intention. This research uses primary data obtained from questionnaires measured with the Likert scale. The sample is the Tiktok App users who have shopped through Tiktok Shop in Manado. Test instruments are performed using Validity and Reliability Tests. The regression results show that digital marketing and sales promotion have a positive and significant effect on purchase intention through Tiktok Shop, while electronic word of mouth exerts no influence on purchase intention.Â Keywords: digital marketing, sales promotion, electronic word of mouth, purchase intention